Tribology and characterization of surface coatings - Ahmed, Sarfraj; Drake, Vinayak S. (Hoboken, NJ : Wiley ; Beverly, MA : Scrivener Publishing, 2022)
Tribology and Characterization of Surface Coatings explores key issues which are important in the research and development of surface coatings by providing updated information on friction and wear behavior of coatings used in different industrial applications. It covers the various coating deposition techniques, tribological response of nanocomposite coatings, multilayer hardfacing, and wear testing methods for coatings at nanoscale. The use of nanostructures may alter the tribological, characterization, and mechanical properties of the materials. Thermal spraying is the most widely used technique in industry for the deposition of coatings and their tribological properties need to be determined. This book also includes the recent trends in biotribology and the materials used in implants to counter the abrasive wear
Overview of Coating Deposition Techniques / Neeraj Mehta -- Tribological Investigation of Developed Nanocomposite Mos2-Tio2-Zro2 Coating Material / Avinash V Borgaonkar, Deepak Rai, Ismail Syed -- Methods of Microstructural Characterization of Coatings / A M Kamalan Kirubaharan, D Dinesh Kumar, K Gobi Saravanan, Subhenjit Hazra -- Wear Mechanisms and Methods of Wear Testing / Ahmed Abdelbary -- Mechanical Behavior of Thermal Spray Coatings / Jayant Gopal Thakare -- Tribological Properties of Carbon-Based Coatings / D Dinesh Kumar, P Kuppusami, Gobi Saravanan Kaliaraj, Siva Sankar Sana, AM Kamalan Kirubaharan -- Performance Evaluation of Journal Bearing Under Thin-Film Lubrication / Sandeep Soni -- Bioactive Coatings for Biomedical Applications / Gobi Saravanan Kaliaraj, D Dinesh Kumar, AM Kamalan Kirubaharan -- Study of Tribological Behavior and Wear Mechanism of Nanocomposite Coatings / Lailesh Kumar, Pankaj Shrivastava, Deepankar Panda, Arka Ghosh, Syed Nasimul Alam -- Investigation of Automotive Disc Brake's Material Based on Tribological Parameters by Using Computational Structural Analysis / Prakash R Arul, R Vijayanandh, G Ramesh, S Hariaran, Y Janardhanan, Kumar M Senthil, P Jagadeeshwaran -- Studies of Nanomechanical and Wear Testing Methods of Thermal Sprayed Coatings / Zulfequar Ali, Ashish Kumar Singh, Omprakash Thakare, Chitrakant Tiger -- Overview of Biological Tissue Properties for Biotribology / L DhiviyaLakshmi, V Muthukumaran -- Mechanical Behavior of Single and Multilayer Hardfacing on Ferrous Alloys / B Venkatesh
BIBINDX
Keywords: Tribology; Surfaces (Technology); Electronic books